Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Sumber Berkat Sempurna: The Influence of Leadership Style and Work Environment on Employee Performance at PT Sumber Berkat Sempurna - Intan Nurmalita; Rosmita Rosmita (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstrack - This study aims to determine: (1) the influence of leadership style on employee performance, (2) the influence of work environment on employee performance, and (3) the simultaneous influence of leadership style and work environment on employee performance at PT Sumber Berkat Sempurna. The research employed a quantitative method with a causal associative approach. The population comprised all 37 employees of PT Sumber Berkat Sempurna, using saturated sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The t-test results show that leadership style significantly affects employee performance, while work environment does not have a significant effect. However, the F-test results indicate that leadership style and work environment together significantly influence employee performance. This study highlights the crucial role of leadership in improving employee performance, while the work environment is not yet a dominant factor. Keywords: leadership style, work environment, employee performance